A comparison of epidemiology and clinical outcomes between influenza A H1N1pdm09 and H3N2 based on multicenter surveillance from 2014 to 2018 in South Korea. Issue 1 (25th August 2020) - Yoon, Jin Gu; Noh, Ji Yun; Choi, Won Suk; Lee, Jacob; Lee, Jin Soo; Wie, Seong‐Heon; Kim, Young Keun; Jeong, Hye Won; Kim, Shin Woo; Park, Kyung‐Hwa; Song, Joon Young; Cheong, Hee Jin; et al.
Abstract: Background: After pandemic, A(H1N1)pdm09 is generally known to be associated with younger adults' infection and greater severity than seasonal A(H3N2) but some inconsistences between recent studies exist. Objectives: We aimed to compare the epidemiology and clinical outcomes of A(H1N1)pdm09 and A(H3N2) to verify and consolidate about the knowledge of known differences of subtypes. Methods: Data were retrospectively collected from the hospital‐based influenza morbidity and mortality surveillance in South Korea in nine tertiary care hospitals, from August 31, 2014, to August 25, 2018. Patients with H1N1pdm09 or H3N2 infection admitted in the emergency room or ward were recruited. Results: A total of 1747 patients had influenza A and were divided into two groups those with A(H1N1)pdm09 (n = 240) and those with A(H3N2) (n = 1507). A(H1N1)pdm09 group had younger age (mean age ± standard deviation 50.0 ± 18.8 in H1N1 vs 53.4 ± 21.1 in H3N2, P  = .030), lower influenza vaccination (27.9% vs 43.9%, P  < .001) and pneumococcal vaccination rates (41.0% vs 51.9%, P  < .001), and fewer underlying diseases (67.5% vs 74.0%, P  = .035) than the A(H3N2) group. Influenza A subtypes were not associated with pneumonia risk (adjusted odds ratios [AOR] of A(H1N1)pdm09: 0.7 [95% confidence interval [CI]: 0.4‐1.2, P  = .172]) and in‐hospital mortality (hazard ratio (HR) of A(H1N1)pdm09: 1.0 (95% CI: 0.3‐3.1, P  = .983)). Influenza vaccination reduced in‐hospital mortality in hospitalized patients (HR: 0.3 (95% CI: 0.1‐0.7), P  = .005). Conclusions: A(H1N1)pdm09 infection was more common in younger patients without significant difference in pneumonia risk and in‐hospital mortality between subtypes. Influenza vaccination was associated with reduced in‐hospital mortality.